Wearable Fetal ECG Monitoring System From Abdominal Electrocardiography Recording (Journal of Pharmaceutical Negative Results, 2022)
To find dangerous situations for the foetus, foetal monitoring during pregnancy is crucial. Cardiotocography is the industry-standard procedure for evaluating the health of a foetus inside the womb (CTG). Unfortunately, CT can only be used in a clinical setting since it calls for experienced doctors and heavy equipment to be used. A novel prototype for foetal monitoring is presented to address the drawbacks of CG, which impede a close and continuous monitoring during the latter weeks of pregnancy. We show a foetal monitor that can be worn at home. It is based on the recording of abdominal ECGs as opposed to Doppler Ultrasounds, which CT uses to find foetal heartbeats. Eight leads implanted in a wearable belt are used by the system to measure the maternal and foetal ECG. An original algorithm was created for recognition. he data collecting circuits, data transmission module, and signal analysis platform that underpin the ECG monitoring system have low input-referred noise, high input impedance, and high resolution. The FECG is separated from the AECG signals using the adaptive dual threshold (ADT) and independent component analysis (ICA) algorithms. Pregnant women in three different positions have their AECGs recorded and evaluated to verify the effectiveness of the proposed approach (supine, seated, and standing). The outcome demonstrates that the suggested technology can record the AECG in various postures with good signal quality and high accuracy in foetal ECG and heart rate data. The performance of the foetal QRS (fQRS) complexes extraction is assessed using the metrics of sensitivity (Se), positive predictive accuracy (PPV), accuracy (ACC), and their harmonic mean (F1). For the fQRS complexes extraction, the average Se, PPV, ACC, and F1 score are 99.62%, 97.90%, 97.40%, and 98.66%, respectively. This study demonstrates a promising use for the suggested technology in foetal health monitoring.